Reducing Illegal Logging through a Chainsaw Buyback and Entrepreneurship Program at Gunung Palung National Park - Nurul Ihsan Fawzi; Jackson Helms; Agus Novianto; Agus Supianto; Angela Meike Indrayani; Nur Febriani (Forest and Society, 2020)
Gunung Palung National Park in Indonesian Borneo, home to 2,500 Bornean orangutans (Pongo pygmaeus ssp. wurmbii), suffers from severe deforestation that is caused by illegal logging. This article aims to analyze the success of an innovative entrepreneurship program in reducing illegal logging in Gunung Palung National Park. This program combines voluntary chainsaw buybacks with capital investment for former loggers to launch a business of their choice.  To analyze the success of this entrepreneurship program, we measured two parameters: (1) transitions of former loggers to sustainable alternative livelihoods and (2) reductions in the number of loggers who log actively inside the park. The average monthly income for participating business partners was 2,923,333 rupiah or $209 USD for new partners who had participated for less than one year and 3,357,778 rupiah or $240 for established partners who had participated for more than one year. This income is about the minimum wage for the local area. The failure rate of the program—defined as the partners that returned to logging—was only 6%, or 3 out of 50 partners. Successful forest conservation, however, requires addressing additional factors beyond reducing the access to logging equipment.